2009
DOI: 10.3844/ajassp.2009.1067.1069
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Ginger Extract on Candida albicans

Abstract: Problem statement:The fungal infections could be life-threatening in immunocompromised patients. Candida albicans is the most frequent fungi in the oral cavity. Approach: The first step for treatment could be done using topical antifungal agents. Nystatine is a choice for mentioned usage but there are some problems in its using including: unfavorite taste, frequency of usage, etc. Finding better replacements is the subject of many studies. Results: This study was carried out to find an alternative for Nystatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…Also, only the methanolic and benzyl alcohol extract of ginger had activity on A. niger. An inhibition zone diameter of 11 mm was obtained with ethanolic extracts of ginger against C. albicans in a study conducted by Atai et al, 2009. Similarly, an IZD of 16 mm was obtained with ethanolic extracts of ginger against C. albicans in a study conducted by Supreetha et al, 2011 [24].…”
Section: Resultsmentioning
confidence: 99%
“…Also, only the methanolic and benzyl alcohol extract of ginger had activity on A. niger. An inhibition zone diameter of 11 mm was obtained with ethanolic extracts of ginger against C. albicans in a study conducted by Atai et al, 2009. Similarly, an IZD of 16 mm was obtained with ethanolic extracts of ginger against C. albicans in a study conducted by Supreetha et al, 2011 [24].…”
Section: Resultsmentioning
confidence: 99%
“…Ginger has been reported to exhibit antibacterial (M. N. J. Gulve & N. D. G. Gulve, 2010;Mohamed et al, 2016), antioxidant (Bellik, 2014), antibiofilm (Kim et al, 2013), anti-gastrointestinal cancer (Prasad & Tyagi, 2015) and antifungal properties (Ficker et al, 2003;Atai et al, 2009). As for O. stamineus, studies have reported on the antioxidant, anti-inflammatory (Akowuah et al, 2004;Yam et al, 2008), antifungal (Hossain et al, 2006) and antibacterial properties of this plant (Ho et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ginger rhizome (Zingiber officinale Roscoe, Zingiberacae) is widely used in food condiments and medical herb around the world. Their compound has properties that improve the functioning of the immune system, anti-tumorigenic, anti-inflammatory, anti-apoptosis, antihyperglycemia, anti-lipidemic (Ali et al, 2008) and antifungal activities (Atai et al, 2009). Recently, instead of antibiotics, we reported that DFG possesses growth-promoting qualities in broiler chicken (Incharoen et al, 2010) and egg-productionpromoting qualities in layer chickens (Incharoen and Yamauchi, 2009).…”
Section: Introductionmentioning
confidence: 99%